Intellectual propety strategy A practical guide to IP management - Brazell, Lorna; Buttrick, Richard; Cowan, Peter; Hunsley, Colin; Jones, Gareth; Kallmes, Paul; McLean, Mike; Mitchell, Nicholas; Ortiz, Josue; Pixton, Ryan; Tame, Alex
Intellectual Property Strategy: A Practical Guide to IP Management: Over the past three decades, the make-up of the market value of Market and Poor 500 companies has changed dramatically. While intangible assets amounted to less than one-third of the company value in the mid-1980s, this has almost tripled to four-fifths in the average today. A large contributor to this trend is intellectual property (IP)- a situation that is even truer for start-up companies, where IP assets may be the only significant asset a company has for quite some time. it is the fore important that company leaders understand the intricacies of IP strategy and how it is an integral part of a successful business strategy. This guide provides a solid grounding in concepts such as IP generation, IP valuation, portfolio management and monetization of IP assets, as well as practical guidance on setting an IP strategy and managing the risk associated with third-party intellectual property.For holistic understanding, less formal IP assets such as trade secrets and brand strategy are covered in addition to patents and trademarks. Topics are introduced clearly and accessibly to provide decision makers with the necessary background to make informed decisions in cooperation with specialists in-house or external advisers. Chapter features include, key pointers, digestible chapter summaries, and helpful diagrams and checklists, as well as case studies to bring theory into sharp practical focus Whether your company is firmly established or just starting out, this accessible guide is essential reading to facilitate informed decision-making in IP issues, I will also provide those working with intellectual property with a high-level overview of current thinking on IP strategy."--